University Social Responsibility and its impact on the consumer in Latin America: A systematic review of the literature 2013-2023. - Olórtegui Alcalde, Luis Miguel; Bernia-León, Walter Christian; Trucíos Maza, Rafael Andrés (LACCEI, 2024)
The present study has the objective of understanding university social responsibility and its impact on consumers in Latin America, through the various strategies that are applied to guarantee and provide a comprehensive quality service. Attracting consumers is not a simple task; therefore, the recognition of their expectations through neuroscience, social networks, and online services makes it possible to value and design more precise programs in the segmentation of the target consumer. At this point, university social responsibility is seen as a pillar that contributes to sustainable development and the well-being of society through the training of professionals who seek to make university management policies increasingly more efficient. The methodology is based on research and an interpretive paradigm, the PRISMA method was demonstrated to transparently document the reason for the review, what the authors developed and what can be done to evaluate this information. Fundamentals and aspects focused on promoting best practices in study centers are prepared in a documentary manner, encouraging the acquisition of knowledge and skills in accordance with the trends of this globalized world.